Hearing loss with positional changes due to spontaneous intracranial hypotension improved with treatment; a case report - Yasui, Keizo; Hasegawa, Yasuhiro; Yamada, Shinichiro (Rinsho Shinkeigaku, 2013)
A 51-year-old woman was admitted to our hospital because of the right ear fullness and orthostatic headache. Based on the findings of low cerebrospinal fluid (CSF) pressure and detected images of CSF leakage by MRI myelography and radionuclide cisternography, she was diagnosed as having spontaneous intracranial hypotension (SIH). Audiograms in the supine and sitting positions showed a marked hearing loss of low-frequencies and its exacerbation after the sitting. After she was treated with bed rest, hydration and epidural blood patch, hearing loss with positional changes gradually improved. In conclusion, non-invasive examinations with audiogram in the supine and sitting positions could be useful in the diagnosis of SIH and the evaluation of therapeutic efficacy of hearing loss.